PERTUMBUHAN PLANLET KRISAN (Dendranthema grandiflora Tzvelev) KULTIVAR PINK FIJI SETELAH PENAMBAHAN EKSTRAK TAUGE (Vigna radiata L.) PADA MEDIUM MURASHIGE DANSKOOG (MS) SECARA IN VITRO. - Nalindri Impitasari; Endang Nurcahyani; Tundjung Tripeni Handayani; Yulianty Yulianty (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Chrysanthemum (Dendranthema grandiflora Tzvelev) is one of the important ornamental plants in Indonesia and has high economic value . This plant is known as a producer of flowers with attractive shapes and colors . Seeing the magnitude of community interest and the potential utilization of chrysanthemum , causing this plant more and more developed and cultivated . This study aims to determine the concentration of optimum mungbean sprouts extract on the growth of chrysanthemum explants in vita . The addition of mungbean sprouts extracts (Vigna radiata L .) from concentration of 0% v/v , 2% v/v , 4% v/v , 6% v/v and 8% v/v on Murashige and Skoog(MS ) medium to growth eksplan Chrysanthemum (Dendranthema grandiflora Tzvelev ) Pink Fiji cultivars have been carried out in the tissue culture laboratory of Faculty of Mathematics and Natural Sciences , University of Lampung from November to December 2017 . This study used Completely Randomized Design (RAL ) 1 factor with 5 replications . Analysis of BNT variety and test is done at 5% level . The results showed that the extract from mungbean sprouts (Vigna radiata L . ) had no effect on plantlet height , number of shoot and number of chrysanthemum (Dendranthema grandiflora Tzvelev) plantlet leaves. The addition of mungbean spourts extracts on Murashige and skoog (MS) medium show 100% live plantlet.